Energy Migration Upconversion in Manganese(II)‐Doped Nanoparticles. Issue 45 (11th September 2015) - Li, Xiyan; Liu, Xiaowang; Chevrier, Daniel M.; Qin, Xian; Xie, Xiaoji; Song, Shuyan; Zhang, Hongjie; Zhang, Peng; Liu, Xiaogang
Abstract: We report the synthesis and characterization of cubic NaGdF4 :Yb/Tm@NaGdF4 :Mn core–shell structures. By taking advantage of energy transfer through Yb→Tm→Gd→Mn in these core–shell nanoparticles, we have realized upconversion emission of Mn 2+ at room temperature in lanthanide tetrafluoride based host lattices. The upconverted Mn 2+ emission, enabled by trapping the excitation energy through a Gd 3+ lattice, was validated by the observation of a decreased lifetime from 941 to 532 μs in the emission of Gd 3+ at 310 nm ( 6 P7/2 → 8 S7/2 ). This multiphoton upconversion process can be further enhanced under pulsed laser excitation at high power densities. Both experimental and theoretical studies provide evidence for Mn 2+ doping in the lanthanide‐based host lattice arising from the formation of F − vacancies around Mn 2+ ions to maintain charge neutrality in the shell layer. Abstract : On the up : The upconversion emission of Mn 2+ ions can be realized in NaGdF4 :Yb/Tm@NaGdF4 :Mn core–shell nanoparticles by utilizing energy migration through the gadolinium sublattice (see figure). The multiphoton upconversion process can be further enhanced under pulsed laser excitation at high power densities. The ability of the Mn 2+ ‐doped nanoparticles to easily undergo oxidization makes them attractive for use in hydrogen peroxide detection.